2017
DOI: 10.3389/fbioe.2017.00042
|View full text |Cite
|
Sign up to set email alerts
|

Force Myography for Monitoring Grasping in Individuals with Stroke with Mild to Moderate Upper-Extremity Impairments: A Preliminary Investigation in a Controlled Environment

Abstract: There is increasing research interest in technologies that can detect grasping, to encourage functional use of the hand as part of daily living, and thus promote upper-extremity motor recovery in individuals with stroke. Force myography (FMG) has been shown to be effective for providing biofeedback to improve fine motor function in structured rehabilitation settings, involving isolated repetitions of a single grasp type, elicited at a predictable time, without upper-extremity movements. The use of FMG, with ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 36 publications
1
34
0
Order By: Relevance
“…This is mostly due to a lack of reliable measurement methods, especially concerning shear forces. Much effort has recently been put into the development of those measurement methods (Lenzi et al, 2011;Sugiura et al, 2012;Makino et al, 2013;Castellini and Ravindra, 2014;Ito et al, 2014;Tamez-Duque et al, 2015;Wilkening et al, 2016;Alavi et al, 2017;Sadarangani et al, 2017). A method that can be considered as the gold standard for measuring normal and tangential forces is the load cell.…”
Section: Introductionmentioning
confidence: 99%
“…This is mostly due to a lack of reliable measurement methods, especially concerning shear forces. Much effort has recently been put into the development of those measurement methods (Lenzi et al, 2011;Sugiura et al, 2012;Makino et al, 2013;Castellini and Ravindra, 2014;Ito et al, 2014;Tamez-Duque et al, 2015;Wilkening et al, 2016;Alavi et al, 2017;Sadarangani et al, 2017). A method that can be considered as the gold standard for measuring normal and tangential forces is the load cell.…”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous studies that investigated the feasibility and accuracy of the approach [ 102 , 103 , 104 , 105 ]. Cho et al demonstrated [ 106 ] the feasibility of this control approach for hand prosthesis control.…”
Section: Approaches Proven For Prosthetic Controlmentioning
confidence: 99%
“…The hands of patients who are affected by significant levels of post-stroke flexor spasticity remain tightly clenched due to the increased muscle tone in finger flexors, which is also believed to be the underlying reason of the difficulty in extending the fingers for stroke patients (Marciniak, 2011). In other words, this spasticity increases stiffness of the finger joints and furthermore leads to a decrease of their range-of-motion (ROM), creating severe reduction to hand function (Sadarangani et al, 2017). As spasticity and motor recovery are both related to neural plasticity after stroke, to lead targeted rehabilitation interventions, it is suggested that clinicians should decide the best treatment option for each patient based on their spasticity condition (Hong et al, 2018;Jeanette et al, 2019).…”
Section: Introductionmentioning
confidence: 99%